Elementary school wellness education an integrated approach to teaching the whole child - Cummiskey, Matthew 1974-; Cleland, Frances E. (Human Kinetics, 2023)
"This book introduces school wellness education (SWE), which combines physical activity and health-enhancing skills into the same lesson. This enables students to receive a more holistic education across multiple domains of wellness. SWE meets multiple learning standards simultaneously and better uses limited class time"--